2007
DOI: 10.1097/mpg.0b013e3180f60b9e
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function Test Results Predict Nutritional Status Evaluated by Arm Anthropometric Indicators

Abstract: The data presented underline the correlation between the liver damage severity evaluated by LFT and the nutritional status estimated by anthropometric indicators. In our view these observations reflect the close relationship between liver function and the degree of liver damage to growth and current nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
5
32
0
4
Order By: Relevance
“…Several studies have shown the direct association of disease, biochemical changes, and nutritional status with upper-arm composition. 13,14 The NF1 nutritional status assessment is relevant, because features of this disease as underweight or short height can influence patients' health and quality of life. Therefore, the present study aimed to assess the body composition of NF1 adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the direct association of disease, biochemical changes, and nutritional status with upper-arm composition. 13,14 The NF1 nutritional status assessment is relevant, because features of this disease as underweight or short height can influence patients' health and quality of life. Therefore, the present study aimed to assess the body composition of NF1 adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…The body-composition allows a quantitative assessment of muscle-mass and adiposity changes that reflects nutritional intake, losses and expenses over timeperiod (1,3,14). Recently, several investigations have shown the direct association of disease, biochemical changes, clinical diagnosis and nutritional status with upper-arm composition (6,25,26). Furthermore, age-sex and population specific upper-arm anthropometry seems to be an important technique to determine body-composition and nutritional status especially in epidemiological, clinical diagnosis and disease prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Foram encontrados sete artigos com menos de 10 anos de publicação passíveis de comparação com o presente estudo: quatro brasileiros [15][16][17][18] e três internacionais [19][20][21] . Esses estudos utilizaram os índices E/I e/ou DCT/I para a classificação do estado nutricional e os modelos PELD e/ou MELD e/ou o escore Child-Pugh para a classificação da gravidade da doença.…”
Section: Resultsunclassified
“…Pode-se verificar que aqueles estudos que apresentaram escores mais altos de gravidade da doença hepática são os que possuem maiores percentuais de pacientes com desnutrição. A exceção é vista no estudo de Hurtado-López et al 19 , que, apesar de encontrar média do PELD baixa, observou que 44,3% dos pacientes apresentaram desnutrição crônica, determinada pelo índice E/I. Nas duas séries deste estudo, os resultados de DCT/I e CB/I com escore-z ≤ -2,00 foram semelhantes e não demonstraram diferença significativa (tabela 2).…”
Section: Discussionunclassified
See 1 more Smart Citation